Endothelial dysfunction in DOCA-salt hypertension - Possible involvement of prostaglandin endoperoxides - Cordellini, S. (Elsevier B.V., 1999)
The effects of the arachidonic acid metabolism inhibitors on the acetylcholine responses of aortae from control (CR) and deoxycorticosterone acetate (DOCA)-salt hypertensive (HR) rats were investigated. The acetylcholine decreased response observed in HR [relaxation (%): CR 95.5 +/- 2.7, n = 4; HR 52.0 +/- 6.3, n = 5, p < 0.05] was restored by the cyclooxygenase inhibitor piroxicam [relaxation (%): CR 99.8 +/- 0.2, n = 4; HR 86.0 +/- 4.0, n = 5] and by the thromboxane synthetase inhibitor and the thrombox ane A(2)/prostaglandin H-2 receptor antagonist ridogrel [relaxation (%): CR 92.1 +/- 4.4, n = 7; HR 93.1 +/- 2.0, n = 7] but not by the inhibitors of thromboxane synthetase, prostacyclin synthetase, cytochrome P-450 monooxygenase, and lipoxygenase. So, endoperoxide intermediates seem to be involved in the decreased endothelium-dependent relaxation to acetylcholine in DOCA-salt hypertension. (C) 1999 Elsevier B.V. All rights reserved.
Keywords: DOCA-salt hypertension; arachidonic acid metabolism inhibitors; endothelium-derived contracting factor; prostaglandin endoperoxide intermediates; rat aorta; acetylcholine